Role of surface to volume ratio of zinc oxide arrester blocks on the energy absorption capability - Karim, A.N. Mustafizul; Begum, Shahida; Hashmi, M. S. J. (2013)
The functional life of a zinc oxide arrester block is largely dependent on its energy absorption capability. This capability is an important performance characteristic of a lighting arrester which leads to enhanced reliability of a surge protection system. An arrester block is usually cylindrical in shape with two flat surfaces. Injected energy of transient electrical surge into the arrester body is transformed into heat and dissipated through the surface of the disc body. This study has been conducted to observe whether the higher surface to volume (S/V) ratio of an arrester block enhances the capability of energy absorption or not. The round side or C-surface of the cylindrical disc was ground by diamond wheel to transform into hexagonal shape. By making the modification of the geometrical shape an increase of about 11% in S/V ratio was achieved. ZnO arrester blocks of both shapes were tested for energy. The average energy absorption capability for the hexagonal discs was found to be 483 J.cm-3 compared to that of 357 J.cm-3 for the discs having the cylindrical shape. Thus, about 35% increase in energy absorption capability is observed for the hexagonal discs. This knowledge can be useful in designing the geometry of the device for improved functional reliability of electrical system.